Quantifying Long-Term Adaptations in Performance Variables in Adolescent Athletes: A 1.5 Year Longitudinal Training Study Utilising a Standardised, Progressive, Blocked Linear Periodisation Resistance Training Program - Michael A. Carron; Vincent J. Dalbo (Sports, 2025)
We examined the effects of resistance training over 1.5 years (two seasons). Body mass, strength, power, and aerobic capacity were assessed during the first 1.5 years of a standardised, progressive, blocked linear periodisation training program in adolescent males with no prior history of resistance training (N = 11, 16.4 ± 0.5 years). Testing occurred during the start of pre-season (SPS), end of pre-season (EPS), and end of season (EOS) during the first and second year of resistance training. Changes over time were assessed with within-group ANOVAs and follow-up independent t-tests. Differences in relative change that occurred during the first and second year of training for each variable were assessed with dependent t-tests. Body mass changed over time (p < 0.001, n2p = 0.794). Body mass increased from SPS to EPS (p = 0.008, Large) and EPS to EOS (p = 0.019, Large) in year 1, and from EOS in year 1 to SPS in year 2 (p < 0.001, Large). Bench press (p < 0.001, n2p = 0.806), squat (p < 0.001, n2p = 0.670), and medicine ball throw (p < 0.001, n2p = 0.350) changed over time. Bench press (Year 1: p < 0.001, Large; Year 2: p < 0.001, Large), squat (Year 1: p < 0.001, Large; Year 2: p < 0.001, Large), and medicine ball throw (Year 1: p = 0.007, Large; Year 2: p = 0.026, Large) increased from SPS to EPS in year 1 and year 2. Bench press (p = 0.010, Large) and squat (p = 0.004, Large) increased more from SPS to EPS during year 1 than year 2. By quantifying diminished returns, our study offers practitioners novel information, helping practitioners manage expectations, avoid excessive training and support long-term adolescent development.